¿Cuánto duraremos? - Claro, Francisco (MOMENTO, 2001)
When physics is asked to make a statement of the end of times t he issue of its real capability for predicting the fut ure is brought about. Here we question such capability and present the concept of a credibility horizon in scientific prediction, which makes explicit the existence of a limited scope to whatsoever statement about t he future. In part icular, the proposit ions of cosmology about t he evolution of the material substrate that makes life posible, or about the end of time, must be read as statements of bounded validity and not as a final truth.